Pengaruh Akuntabilitas dan Transparansi terhadap Kualitas Laporan Keuangan pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Tebo - Anggraini, Suci; Mutia, Agustina; Putriana, Marissa (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the effect of accountability and transparency on the quality of financial reports at the Tebo Regency National Zakat Amil Agency (BAZNAS). This research uses quantitative methods. The analytical methods used are descriptive statistics, data quality testing, classical assumption tests, multiple linear tests and hypothesis testing. The data for this research are primary data and secondary data. The data collection technique used a questionnaire and the sample in this study was 32 amil who were tasked with managing zakat at the Tebo Regency National Zakat Amil Agency (BAZNAS) using a Purposive Sampling sampling technique. The results of this research show that the accountability variable partially has a significant effect on the quality of financial reports, and the transparency variable also partially has a significant effect on the quality of financial reports. And simultaneously the variables of accountability and transparency have a significant effect on the quality of financial reports at the Tebo Regency National Zakat Amil Agency (BAZNAS).